Efektivitas Program SIPRAJA Sebagai Inovasi Pelayanan Publik di Kecamatan Sidoarjo Kabupaten Sidoarjo - Saputra, Dema Prayuda; Widiyarta, Agus (Universitas 17 Agustus 1945 Surabaya, 2021)
Public services according to Article 1 paragraph (1) of Law Number 25 Year 2009 are activities or a series of activities aimed at meeting the service needs of every community and population for goods, services & administrative services provided by the state as public service providers.in an effort to realize a public service innovation through its flagship program, namely SIPRAJA. This study aims to determine the effectiveness of the SIPRAJA program as a public service innovation in Sidoarjo District, Sidoarjo Regency. In this research, the type of research used is descriptive research with qualitative methods. Overall the SIRPAJA program in Sidoarjo District, Sidoarjo Regency has been effective. However, if there are technical problems in the following applications and there are people who choose to do offline, the author's advice is that the operator still helps to register it and guide the community to perform services through the SIPRAJA program. However, if there are technical problems in the following application and there are people who choose to do it offline, the author's suggestion is that the operator can still help to register it and guide the community to perform services through the SIPRAJA program.